The importance of Mussidia nigrivenella ragonot (Lepidoptera: phralidae) as a postharvest pest in different storage structures in Benin - Agboka, K.; Schulthess, F.; Tamo, Manuele; Hell, K.; Vidal, S. (Elsevier, 2010)
In West Africa, the most damaging lepidopteran pest of maize ears is the pyralid Mussidia nigrivenella. Although it is mostly described as a field pest, it can be found feeding on maize stored for up to 4 months. A survey was conducted in Benin in 2006 to assess M. nigrivenella infestations in different maize storage systems in the Southern (SGS) and Northern Guinea Savanna (NGS). In SGS and NGS the percentage of infested stores decreased from 86.7% to 26.7% and from 51.4% to 14.3%, respectively, during the first 28 weeks of storage. During the same time, mean numbers of M. nigrivenella per cob decreased from 0.36 to 0.04 across both zones. All larval stages, but mostly 3rd–5th instars, were frequently found even after more than 12 weeks, indicating that M. nigrivenella may have reproduced in storage, although reinfestation or delayed development could also explain this observation. The highest M. nigrivenella incidences of 16.8% and 14.4% were found in the “Ava” and crib stores, respectively. Infestations were highest in “Ava” and lowest in maize grain stored in polyethylene bags or in mud silos. In a laboratory experiment, the presence of post-harvest beetles negatively affected the bionomics of M. nigrivenella, indicating strong interspecific competition.